The effect of sowing time on productivity of new maize hybrids - Kh. Sh. Tarchokov; O. Kh. Mataeva; F. Kh. Bzhinaev; N. V. Berbekova (Зерновое хозяйство России)
The relevance of the current study is due to the fact that global warming in the south of Russia has significantly moved forward the onset of the hot period, especially in areas of risky farming. Sowing at the previously recommended scientifically based optimal time no longer guarantees stable yields of maize. Based on this, the purpose of the study was to determine the effect of the sowing time of new promising maize hybrids of our own breeding on productivity and yield structure elements in the steppe part of Kabardino-Balkaria. The study was carried out in field trials on the field of the research and production site of the Institute of Agriculture of the KBRC of the Russian Academy of Sciences in 2019–2021. In general, during the years of study, weather conditions were typical for the steppe area of the KBR. As a result, there was determined that the optimal sowing time for maize hybrids was the second decade of April. When sowing at this time, there was identified productivity improvement and an increase in the values of yield elements. On the contrary, sowing in the third decade has shown a decrease in the values of these indicators in all studied samples. During the second sowing period, there was the greatest productivity decrease among the late-maturing hybrids ‘Karat SV’, ‘Terek’ and the hybrid population ‘Kabardinskaya 3812’ by 1.4; 1.5 and 1.8 t/ha, respectively. The middle-early hybrid ‘Maisky 260 MV’ has shown a smaller decrease by 0.7 t/ha. During the first sowing period, number of ears per 100 plants increased by 4–11 pieces. The ears were better grained with 5–60 pieces of the excess over the second period. The weight of one cob during the first sowing period ranged 105–120 g on average, which was 9–22 g more than the same indicator during the second sowing period.